Colour removal of raw carrageenan by using sodium hypochlorite as bleaching agent - Norazlinda, Hanen (2013)
Carrageenans are natural ingredients that represent one of the major texturizing ingredients used by the food industry. However, the extracted carrageenans from seaweeds may have colour such as light brown. These criteria will affect marketed sector because the product are not presented in an interesting ways. Therefore, sodium hypochlorite is one of the effective treatment options and it has potential for removing of colour as bleaching agent. This is due to chlorine is the basis for the most common material used on bleaching. However, the availability of chlorine will give unpleasant odour to the product. This problem can be overcome by addition of sodium thiosulfate into the seaweed to neutralize the sodium hypochlorite. The purpose of this study is to remove colour of carrageenan from seaweed. Amount of sodium hypochlorite are the variable need to be controlled in order to get the optimum condition removing colour of extracted carrageenan from seaweed. When the amount of sodium hypochlorite increased, the time needed to decolourizing carrageenan become more faster. However, by using chlorine bleach (sodium hypochlorite) as a bleaching agent in food processing, this operations must follow permissible regulations to dealing with health effect.